Estilos de personalidad y afrontamiento en madres de niños hospitalizados. área neonatología. Hospital Provincial General Docente Riobamba, 2018. - Francisca Paola, Burgos Berrones, Enma Cristina, Gavilanes Velásquez (2019)
The present study aims to analyze personality styles and how mothers cope of their children´s care who have hospitalized at Neonatology area in Hospital Provincial General Docente Riobamba. This research was carried out by collecting data from Clinical records. Therefore, it is a bibliographic, a non-experimental, and an exploratory research under a transversal desing. The population consists of 30 adult mothers who were registered with their medical records. The technique used is the observation and the instruments used were an observation guide called: Million Personality Styles Inventory (MIPS) in order to measure the Personality Styles variable; in the other hand, an observation guide of the Inventory of Coping Strategies (CSI) was employed in order to determine Coping Strategies. The obtained results showed that 23.33% out of 100% mothers has a Sensation Personality Style. Likewise, 60.00% out of 100% of them employ Negation to Reality Strategy. Based on the obtained results, the researchers elaborated some Coping strategies on a diptych for informing about how to cope with children´s care under stress situation.